Spontaneous Rupture of Hepatic Metastasis from Pancreatic Adenocarcinoma - Anil Rahul; Fernandes Robin; Hiremath Adarsh (Case Reports in Oncological Medicine)
A 58-year-old man with advanced-stage pancreatic adenocarcinoma presented with fatigue and dyspnea. Examination revealed tachycardia (102 b/min) with mild tenderness in right upper quadrant. His hemoglobin (Hb) was 7.9 g/dL (10 days prior to presentation 12.2 g/dL), International normalized ratio (INR), platelet count was normal, and the stool guaiac test was negative. On admission, abdominal computed tomography (CT) scan showed hepatic metastatic lesion with a rupture and hemoperitoneum communicating to the subdiaphragmatic space. This rapid progression of anemia along with presenting symptoms and CT imaging were attributed to diagnosis of spontaneous rupture of liver metastasis from pancreatic adenocarcinoma. Patient received blood transfusion and hemoglobin was monitored in successive intervals. His general condition and anemia improved with conservative management and he was discharged in 3 days. Repeated CT after 4 months showed resolving hemoperitoneum and stable hemoglobin levels. The patient deceased 9 months after being diagnosed. A literature search revealed limited data regarding the incidence and management of spontaneous rupture of metastatic lesion secondary to pancreatic adenocarcinoma which has been managed conservatively and thus we are reporting our experience.